"Heartbreaking" Referrals, Professional "Disgrace": The Impact of Medicare Ineligibility on the Counseling Profession. Issue 1 (8th April 2020) - Fullen, Matthew C.; Wiley, Jonathan D.; Jordan, Justin; Sharma, Jyotsana; Lawson, Gerard
Abstract : To better understand the impact of the Medicare mental health coverage gap, the authors analyzed survey data provided by 1, 859 members of the American Counseling Association using a conventional qualitative content analysis. One overarching theme, direct impact of Medicare policy on the counseling profession, is presented, along with 3 thematic categories: emotional impact on providers, economic toll on providers, and negative influence on profession's credibility. Implications for the counseling profession are discussed.